A Study about Customer Relationship Quality among Kopi Kenangan Consumers in Indonesia - Ratni Prima Lita; Laura Amelia Triani; Husnul Khatimah (Jurnal Manajemen dan Kewirausahaan, 2025)
The coffee shop industry in Indonesia is growing rapidly due to the wide availability of coffee and high domestic demand. However, leading brand Kopi Kenangan faces strong competition from both local and international players, resulting in a decline in brand index and fluctuating sales. Building strong customer relationships through visual branding, especially the brand logo, becomes important. This study examines how brand logo benefits influence customer relationship quality, with brand stereotypes as a mediating variable. A quantitative approach with purposive sampling was applied to select 200 respondents who had purchased Kopi Kenangan products within the past three months. Data were collected through an online questionnaire and analyzed using the structural equation modelling technique. The results indicate that aesthetic and self-expressive benefits positively affect warmth and competence stereotypes. These stereotypes, in turn, significantly improve trust, satisfaction, and commitment, although the mediation effect is consistent only for aesthetic benefits. The findings suggest that companies should ensure consistent and visible logo use across marketing channels to strengthen brand stereotypes and enhance long-term customer relationships.